Pola Asuh Dan Perkembangan Mental Emosional Anak Korban Keluarga Broken Home Di Lembaga Kesejahteraan Sosial Anak Panti Asuhan Muhammadiyah Ponorogo - Agung Sumbawa; Syahrudin; Bagaskoro Trisno Dwi Wibowo (IKTIFAK: Journal of Child and Gender Studies, 2023)
Parenting is very important in shaping the character of the child in the future. Correct parenting can affect the mental emotional development process of children, especially those from broken home families, the mental emotional development of children must be monitored intensively and lovingly, here the Social Welfare Institution Muhammadiyah Ponorogo Orphanage children have implemented a system of correct parenting for children who are victims of broken home families, The formulation of the problems that we can take are: (1) how is the parenting style of children in the Muhammadiyah Ponorogo orphanage children's social welfare institution 2) how is the mental emotional development of children in the social welfare institution of Muhammadiyah Ponorogo orphanage children (3) how is parenting patterns and emotional mental development child victims of broken home families at the Muhammadiyah Ponorogo orphanage child social welfare institution, This study used a qualitative (descriptive) method, with the teacher object of the parenting section as a data source and the orphanage dormitory building as a field data object, the results of this study were (1)Parenting Methods using Democratic Methods, (2) Emotional Mental Development of victim children from broken home families using the first 6 month term program, namely environmental adaptation, the next is a 1-1.5 year program, namely education and character building, (3) In carrying out the parenting program, parenting applies the democratic method or by means of kinship, while in the mental emotional development of children, parenting applies a program of the first 6 months and 1 - 1.5 years. This program is considered successful with the best graduates of an orphanage named EW who can continue to Higher Education Faculty of Medicine.